The Middle Passage : Comparative Studies in the Atlantic Slave Trade - Klein, Herbert S. (Princeton, NJ : Princeton University Press, 1978)
Herbert Klein's book makes several distinctive contributions to our understanding of the slave trade. It offers us the first systematic comparative study of major European slave traders based exclusively on archival sources. The author's minimization of the effect of overcrowded slave ships contributes to a longstanding debate regarding the mortality rate of the slaves. His emphasis of the African influences on the character of the slave trade offsets the more frequent emphasis placed on the European influences. Furthermore, Klein maintains that basic similarities existed among the slave-trading practices of all nations, with no one nation being any better than another.Using demographic and other quantitative data, Professor Klein describes the trans-Atlantic slave trade as it was practiced by all of the major European powers during the period of its maximum development. His work spans a century and a half of European trading activity and an area from Senegal to Mozambique in Africa and from the Chesapeake to Guanabara Bay in the Western hemisphere.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Table of Contents -- List of Tables and Graphs -- Introduction -- Abbreviations -- Chapter One. The American Demand for Slaves and the Afro-American Patterns of Settlement -- Chapter Two. The Portuguese Slave Trade from Angola in the 18th Century -- Chapter Three. The Trade in African Slaves to Rio de Janeiro, 1795-1811 -- Chapter Four. Shipping Patterns and Mortality in the African Slave Trade to Rio de Janeiro, 1825-1830 -- Chapter Five. The Internal Slave Trade in 19th-century Brazil -- Chapter Six. Slaves and Shipping in 18th-Century Virginia -- Chapter Seven. The English Slave Trade to Jamaica, 1782-1808 -- Chapter Eight. The French Slave Trade in the 18th Century -- Chapter Nine. The Cuban Slave Trade in a Period of Transition, 1790-1843 -- Chapter Ten. Conclusion -- Appendices -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Slave trade -- History; SOCIAL SCIENCE / Slavery